Oxidative stress in the medullary respiratory neurons contributes to respiratory dysfunction in the 6-OHDA model of Parkinson's disease - Falquetto, Bárbara; Thieme, Karina; Malta, Marília B.; e Rocha, Karina C.; Tuppy, Marina; Potje, Simone R. [UNESP]; Antoniali, Cristina [UNESP]; Rodrigues, Alice C.; Munhoz, Carolina D.; Moreira, Thiago S.; Takakura, Ana C. (Wiley, 2020)
Key points: Parkinson's disease (PD) is associated with respiratory dysfunction. In the 6-OHDA rat model of PD this is seen as a reduction in respiratory frequency and minute ventilation during normoxia and hypercapnia stimulus. Respiratory dysfunction is caused by neuronal death of medullary respiratory nuclei in the 6-OHDA model of PD. Oxidative stress can be considered a strong candidate for neurodegeneration via miR-34c downregulation and pro-apoptotic signalling in respiratory neurons, preceding the functional impairment observed in the 6-OHDA model of PD. Abstract: Parkinson's disease (PD) is a neurodegenerative disease caused by dopaminergic neuron death in the substantia nigra (SN). New evidence has revealed that this neurodegeneration is the result of complex interactions between genetic abnormalities, environmental toxins, mitochondrial dysfunction and disruption of the blood–brain barrier (BBB) in the SN. In addition to classic symptoms, PD patients also exhibit respiratory failure. Here, we investigated whether oxidative stress was associated with neurodegeneration in a respiratory group (RG) of 6-OHDA-treated rats, which act as a model of PD. We analysed how oxidative stress affected apoptotic signalling in the RG 30 days after 6-OHDA treatment, shortly before commencement of breathing impairment (40 days). After 30 days, a dihydroethidium assay showed increased oxidative stress in the RG, anti-apoptotic signalling, as shown by an increase in p-Akt and BcL-2 and a decrease in Bax in the caudal aspect of the nucleus of the solitary tract (cNTS), and a decrease in p-p38 and Bax levels in the retrotrapezoid nucleus (RTN); pro-apoptotic signalling was indicated by a decrease in p-Akt and BcL-2 and an increase in Bax in the rostral ventral respiratory group (rVRG) and pre-Botzinger complex (preBotC). miR-34c, a known oxidative stress protector, was downregulated in 6-OHDA animals in the RC. After 40 days of 6-OHDA, the NTS, rVRG, preBotC and RTN exhibited reduced NeuN immunoreactivity, no BBB disruption and an increase in thiobarbituric acid reactivity. We conclude that in the 6-OHDA model of PD, oxidative stress contributes to neurodegeneration in medullary respiratory neurons.
Keywords: 6-OHDA; apoptosis; breathing control; medulla; miRNA; oxidative stress